Fish and macro-crustacean assemblages are relevant ecological indicators for monitoring rivers of tropical islands - Nils Teichert; Raphaël Lagarde; Laëtitia Faivre; Pierre Valade; Henri Grondin; Marion Labeille; Philippe Keith; Eric Feunteun (Ecological Indicators)
Understanding how tropical rivers change in response to human-induced disturbances represents a major challenge for management and conservation. However, monitoring networks based on ecological indicators remain scarce in oceanic islands, where freshwater indigenous fish and macro-crustacean assemblages are dominated by diadromous species. We investigated the relevance of these taxa for assessing the ecological status of rivers in two tropical islands, Reunion and Mayotte, Indian Ocean, to fulfill objectives of the European Water Framework Directive in overseas regions. Beyond providing insights on ecological responses of fish and macro-crustacean assemblages, we proposed a methodological framework to designed stressors-specific multimetric index by selecting primarily shared metrics between and within islands to improve the robustness and interpretation of this index. Numerous candidate metrics were tested to reflect the alterations induced by three stressors categories (i.e., continuity alteration, agricultural and urbanisation stresses) on the diversity, abundance, or size-structure of assemblages. Our results demonstrated that fish and macro-crustacean assemblages were sensitive to multiple stressors, but the ecological responses were more congruent when facing continuity alterations, compared to land use changes associated with agriculture or urbanization. These migratory species are understandably vulnerable to river fragmentation, but their oceanic dispersive stage favor exchanges between watersheds, which in turn can promote the resilience and persistence of local populations in degraded areas. In such insular context, we thus suggested using fish and macro-crustaceans to firstly assess the state of ecological continuity, whereas other taxa, such as diatom or macroinvertebrates, can be complementary to reflect the alteration of water quality.